The Cambridge companion to Augustine - Stump, Eleonore (The Cambridge companions to philosophy, religion and culture, 2001)
It is hard to overestimate the importance of the work of Augustine of Hippo, both in his own period and in the subsequent history of Western philosophy. Until the thirteenth century, when he may have had a competitor in Thomas Aquinas, he was the most important philosopher of the medieval period. Many of his views, including his theory of the just war, his account of time and eternity, his understanding of the will, his attempted resolution of the problem of evil, and his approach to the relation of faith and reason, have continued to be influential up to the present time. In this 2001 volume of specially-commissioned essays, sixteen scholars provide a wide-ranging and stimulating contribution to our understanding of Augustine, covering all the major areas of his philosophy and theology.